PENGARUH BUDAYA KAIZEN TERHADAP KINERJA KARYAWAN PT. INDOSPRING, TBK DI GRESIK - Kusumaningrum, Dini; Muhtadin, Muhtadin (GEMA EKONOMI, 2017)
This study aims to determine and clarify the picture of the implementation of Kaizen culture, and employee performance in PT. Indospring, Tbk effect of applying Kaizen Culture the performance of employees at PT. Indospring, Tbk: this type of research used in this research is explanatory research with quantitative approach variables in this research is the application of Culture Kaizen as an independent variable, and the employeeÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s performance as the dependent variable this study uses data printer is the form of the answers to the questionnaire and secondary data Through documents. Data analysis method used is descriptive analysis. The result of descriptive analysis shows that there is significant influence between Kaizen Culture implementation variables. There is a significant influence between the variables of cultural implementation of Kaizen culture on employee performance.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477683